Sung poems and poetic songs: Hellenistic definitions of poetry, music and the spaces in between - Klavan, SA (Cambridge University Press, 2020)
Simply by formulating a question about the nature of ancient Greek poetry or music, any modern English speaker is already risking anachronism. In recent years especially, scholars have reminded one another that the words ‘music’ and ‘poetry’ denote concepts with no easy counterpart in Greek. μουσική in its broadest sense evokes not only innumerable kinds of structured movement and sound but also the political, psychological and cosmic order of which song, verse and dance are supposed to be perceptible manifestations.1 Likewise, ποίησις and the ποιητικὴ τέχνη can encompass all kinds of ‘making’, from the assembly of a table to the construction of a rhetorical argument.2 Of course, there were specifically artistic usages of these terms—according to Plato, ‘musical and metrical production’ was the default meaning of ποίησις in everyday speech.3 But even in discussions which restrict themselves to the sphere of human art, we find nothing like the neat compartmentalization of harmonized rhythmic melody on the one hand, and stylized verbal composition on the other, which is often casually implied or expressly formulated in modern comparisons of ‘music’ with ‘poetry’.4 For many ancient theorists the City Dionysia, a dithyrambic festival and a recitation of Homer all featured different versions of one and the same form of composition, a μουσική or ποιητική to which λόγοι, γράμματα and συλλαβαί were just as essential as ἁρμονία, φθόγγοι, ῥυθμός and χρόνοι.5